Religion and its Integration in Everyday Life: Public Discourse, Ethical Reasoning, Economic Survival, and Digital Mediation in Contemporary Societies - Scharnick-Udemans, Lee-Shae Salma (Journal for the study of religion, 2025)
It is with great pleasure that we present this edition of the Journal for the Study of Religion (JSR) which focuses on religion as embedded in everyday life, public discourse, ethical reasoning, economic survival, and digital mediation. Since its founding in 1993, the journal has occupied a distinctive and valued place in the academic study of religion in Southern Africa. As a bi-annual, open-access journal affiliated with the Association for the Study of Religion in Southern Africa (ASRSA), JSR remains committed to fostering accessible, rigorous, and contextually grounded scholarship, particularly from and about the Global South. In a scholarly landscape still largely shaped by Global North priorities, this commitment is not only significant, it is urgent and essential. From its inception, JSR has sought to provide an academic home for work attentive to the diversity of religious traditions, movements, and formations in Southern Africa and beyond. The journal has consistently fore-grounded lived realities, comparative perspectives, and critical engagements with religion as it intersects with social, political, economic, and cultural life. This orientation continues to guide the journal's editorial vision, even as the terrain of religion and scholarship shifts in response to changing social conditions, media environments, and global challenges.